Green Product Quality Supervision Strategy in Online Shopping With Consumer Evaluation and Complaint - He, Hui; Zhang, Siyi; Zhu, Lilong (Frontiers in Environmental Science, 2021)
Green consumption is an important foundation for achieving stable and long-term economic development goals. With the rapid development of e-commerce and people’s widespread attention to sustainability, more and more consumers purchase green product online. Therefore, we consider consumer feedback mechanism including evaluation and complaint, and construct an evolutionary game model of green product quality supervision with the participation of governmental supervision department, third-party e-commerce platform, online seller and consumer, which analyzes the four parties’ evolutionary stable strategies. To verify the theoretical results, we conduct a numerical simulation by Matlab 2020b. Moreover, we study the conditions that make evolutionary stable strategy combination exist based on the Lyapunov’s First Method. And we find that when consumer chooses complaint, (0, 0, 1) is likely to become an only evolutionary stable strategy combination. At this time, online seller chooses to provide high-quality green product, third-party e-commerce platform chooses not to strengthen inspection, and governmental supervision department chooses to strictly supervise. Conversely, when consumer chooses no complaint, (1, 0, 0) and (0, 0, 1) may become evolutionary stable strategy combination. At this time, online seller cannot be stable in providing high-quality green product. What's more, governmental supervision department increases the penalty, which can incentivize third-party e-commerce platform to strengthen inspection. Third-party e-commerce platform increases the reward can promote online seller to provide high-quality green product. On the one hand, this paper enriches the theoretical basis of online shopping green product quality supervision. On the other hand, compared with existing literature, it extends the main body of the evolutionary game to four paries, and broadens the application scope of the game model. In addition, it has put forward feasible suggestions for the government supervision department to strengthen the quality supervision, and provided decision-making support for the third-party e-commerce platform to assume the responsibility of quality inspection.